Industrial training report: Hospital Canselor Tuanku Muhriz / Ainul Wardiah Samsol - Samsol, Ainul Wardiah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This industrial training report highlights an eigth week internship experience at the Public Health Department of Hospital Canselor Tuanku Muhriz. The training focused on applying theoretical knowledge to real-world tasks, enhancing skills in report writing, teamwork, and using tools like Canva and Excel. Activities included assisting in health programs like IKMAS, preparing reports, and managing event logistics for the 10th International Public Health Conference. Key learnings involved public health practices, patient confidentiality, and organizational operations. While the internship provided valuable exposure, the report suggests extending the duration to allow deeper learning and involvement. This experience significantly improved technical skills, adaptability, and professional confidence, bridging the gap between academic studies and workplace demands.